Defensive medicine, liability insurance and malpractice litigation in an evolutionary model. (June 2019) - Antoci, Angelo; Maccioni, Alessandro Fiori; Galeotti, Marcello; Russu, Paolo
Abstract: We analyse the relations between defensive medicine, medical malpractice insurance and litigious behaviours, by an evolutionary game between physicians and patients. When medical treatment fails, patients may suit the physician and seek compensation. Conversely, physicians may prevent negligence charges by practising defensive medicine or by buying medical malpractice insurance. The latter choice transfers the risk of litigation from the physician to the insurer. By studying the population dynamics, we intend to describe how clinical and legal risks can shape the interactions between healthcare providers and patients, and how this can affect the diffusion and the price of medical malpractice insurance.